Terminal de transporte multimodal para la ciudad de Ibagué (2023)
The following text is based on a historical analysis of Ibagué, a city that previously it lacked a transport terminal. At that time, the main point of displacement of passengers met in the El Carmen neighborhood, specifically on 21st Street with Carrera 6, where the company called Velotax operated. However, in the 1980s, they were demolished the facilities of the train station initially located on calle 19 with avenida railway. This gave rise to the creation of a new transport terminal in the city of ibagué